Proza Anny Fein. Rosyjsko-izraelska odsłona humoru żydowskiego - Michalska-Suchanek, Mirosława (Studia Rossica Posnaniensia, 2022)
Jewish humour with a rich repertoire of forms is an integral part of Jewish culture. The article summarises the typical features of Jewish humour and presents an outline of its history from its beginning at the turn of the 19th to the 20th century in the countries of Central and Eastern Europe, through the times of immigrants to Palestine, from the first Aliyah (1882–1903), until the establishment of the state of Israel in 1948, to the humour of modern Israel. The humour of Anna Fein – one of the important representatives of Russian-Israeli literature – is situated at the intersection of traditional Jewish humour, Israeli humour, and the mentality of a repatriate (the writer left Russia for Israel during the so-called Great Aliyah), creating an interesting Russian-Israeli version of Jewish humour. Fein’s humour fits in with the exemplary tone of archetypal Jewish humour. At the same time, referring not to the emotions, but to the recipient’s intellect, together with the assumption that humour must have pragmatic values, understood as the implementation of a utilitarian function, it brings the recipient closer to the postulates of Henri Bergson’s theory of laughter.